Prognostic value of future liver remnant LU15 index of (99m)Tc-galactosyl serum albumin scintigraphy for predicting posthepatectomy liver failure - Tomita, Koichi (PLoS One, 2021)
There is no gold standard indicator that is currently used to predict posthepatectomy liver failure (PHLF). A novel indicator of liver function, the LU15 index of (99m)Tc-galactosyl serum albumin (GSA) scintigraphy, refers to the liver uptake ratio over a 15-min interval. We aimed to evaluate the usefulness of the future liver remnant (FLR)-LU15 in predicting PHLF. The clinical data of 102 patients (70 males and 32 females; median age, 70 years) who underwent liver resection between January 2011 and August 2019 were analyzed. The FLR-LU15 was calculated by a fusion of simulated 3-dimensional images and (99m)Tc-GSA scintigraphy. PHLF was determined according to the definition of the International Study Group of Liver Surgery. The FLR-LU15 was an independent risk factor for PHLF ≥ Grade B according to multivariate analysis, and its value correlated with the PHLF grade. The area under the receiver operating characteristic curve of the FLR-LU15 for PHLF ≥ Grade B was 0.816 (95% confidence interval, 0.704–0.929), which was better than that of other indicators. When the cut-off value of FLR-LU15 was set at 16.7, the sensitivity was 86.7%, specificity was 74.7%, and odds ratio was 19.2 (95% confidence interval, 4.0–90.9), all of which were superior to other indicators. If the cut-off value was 13, the positive predictive value was 57.1%. The FLR-LU15 is a useful predictor of PHLF and may be more reliable than other predictors.